2013
DOI: 10.3171/2013.2.focus12398
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral versus bilateral percutaneous pedicle screw fixation in minimally invasive transforaminal lumbar interbody fusion

Abstract: Object Clinical results for unilateral pedicle screw fixation after lumbar interbody fusion have been reported to be as good as those for bilateral instrumentation. However, no studies have directly compared unilateral and bilateral percutaneous pedicle screw fixation after minimally invasive surgery (MIS) for transforaminal lumbar interbody fusion (TLIF). The purpose of this study was to determine whether unilateral percutaneous pedicle screw fixation is comparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 29 publications
2
48
1
Order By: Relevance
“…Five studies compared unilateral with bilateral instrumentation using open transforaminal or posterior lumbar interbody fusion (TLIF/PLIF),6 7 8 9 10 one study used open posterolateral fusion,3 and four used minimally invasive TLIF/PLIF11 12 13 14 (Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…Five studies compared unilateral with bilateral instrumentation using open transforaminal or posterior lumbar interbody fusion (TLIF/PLIF),6 7 8 9 10 one study used open posterolateral fusion,3 and four used minimally invasive TLIF/PLIF11 12 13 14 (Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…Bilateral pedicle screw fixation after MIS TLIF is generally accepted as a standard procedure for symptomatic spinal pathology treatment, [79] but many clinical trials have reported positive outcomes (short operation time, less blood loss, and short hospital stay) associated with unilateral pedicle screw fixation after conventional TLIF and MIS TLIF [1012]. Although previous reports showed that unilateral pedicle screw fixation after MIS TLIF is comparable to bilateral screw fixation, we already reported that less fusion rate (unilateral 84.6%; bilateral 96.3%) and more postoperative scoliosis change rate (unilateral 23.1%; bilateral 3.7%) with unilateral screw fixation than bilateral screw fixation after MIS TLIF [20]. The authors reported in a previous study that numerous degenerative disc diseases are associated with instability, which supports the report that bilateral screw fixation has better outcomes than unilateral screw fixation [20].…”
Section: Discussionmentioning
confidence: 99%
“…MIS TLIF itself needs time to overcome learning curve, and from previous studies, we already know that it needs more than 20 cases experience in MIS TLIF to overcome learning curve [26, 28]. The authors started MIS TLIF from 2008 and previous results of MIS TLIF as primary surgery by us were already reported [6, 20] and experienced more than 100 cases MIS TLIF before starting this study, so we are sure that learning curve did not make any problems at this study.…”
Section: Discussionmentioning
confidence: 99%
“…The retractor was angled medially, The patient was tilted laterally to decompress the contralateral side. Extensive decompression was performed, which included decompression of the central stenosis and contralateral side 1,6,9) . A discectomy was also performed.…”
Section: Technique For Mis Tlifmentioning
confidence: 99%